Dielectric Properties and Microstructure of Sintered BaTiO3 Using 80 nm Particles with Variation of Additives for MLCCs - Oh, M.W.; Shin, H.S.; Yeo, D.H.; Jeong, D.Y. (Asian Journal of Chemistry, 2014)
For the purpose of ultra-thin layer MLCC application, a commercial BaTiO3 dielectric powder with an average particle size of 80 nm was used to apply additives, such as Dy, Mg, Mn, Si, Ba and Ca, by a coating method and the microstructure and dielectric properties of BaTiO3 sintered materials were investigated, as a function of the employed additives. Fixing Mn and Dy ions at 0.2 and 0.75 mol %, respectively and additionally varying Si and Mg from 1 to 1.5 mol % and from 1 to 2 mol %, respectively, the additives were sintered in a reducing atmosphere. Based on the results of an investigation of dielectric properties, Ba 1 mol % and Ca 1 mol % were added and Si and Mg ions were also added to check whether they are applicable to the MLCC composition. With an increase in the amount of Si added, grains were found to grow. In the case of Mg, the grain growth was not controlled even when its amount was increased to 2 mol %. On the other hand, with the addition amount of 2.5 mol %, the grain growth was controlled, consequently resulting in a microstructure having particles with uniform size. The composition with added Ca and Ba, which is known as a depressor, led to large grain growth. Consistent dielectric properties were identified according to changes in grain size and densification and the composition with added Mn (0.2 mol %), Dy (0.75 mol %), Si (1.5 mol %) and Mg (2.5 mol %) met the condition of X6S, temperature dependencies of dielectric constant, having uniform microstructure and reaching a dielectric constant of over 2000 at room temperature.